PENERAPAN KEPEMIMPINAN PARTISIPATIF DALAM PENGEMBANGAN KINERJA ADMINISTRASI DI KANTOR PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) KOTA JAKARTA - Idris, Julizar (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2024)
This study aims to analyze the impact of participative leadership on administrative performance in the Community Learning Center (PKBM) offices in Jakarta. Data were collected through in-depth interviews and direct observations from five PKBMs in Jakarta, involving 20 informants, including PKBM heads, administrative staff, and program managers. The study found that participative leadership significantly contributes to the improvement of administrative performance. Informants revealed that participative leadership enhances communication and relationships within teams, making staff feel more valued and involved in decision-making processes. This involvement positively influences their work spirit and productivity. For instance, in one PKBM, the use of group discussions to formulate human resource management policies led to improved efficiency and minimized communication issues in implementing non-formal education programs. Additionally, PKBM heads practicing participative leadership were found to be more open to feedback, allowing staff to contribute in planning and executing programs. However, the study also identified challenges, including time constraints and limited resources, which hinder the frequency of meetings involving all team members. Despite this, the overall findings support that participative leadership positively influences administrative performance in PKBMs.